2012
DOI: 10.1088/1674-0068/25/04/373-378
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of 2-Bromobutane at ∼265 nm by Ion-velocity Map Imaging Technique

Abstract: The photodissociation dynamics of 2-bromobutane has been investigated at 264.77 and 264.86 nm by ion-velocity map imaging technique coupled with resonance-enhanced multiphoton ionization. The speed and angular distributions have been derived from the velocity map images of Br and Br *. The speed distributions of Br and Br * atoms in the photodissociation of 2-bromobutane at ∼265 nm can be fitted using only one Gaussian function indicating that bromine fragments were produced via direct dissociation of C−Br bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Both photofragments can be observed separately by resonance-enhanced multiphoton ionization (REMPI). Recent studies with nonoriented molecules have reported 38,39 that these two states show independent photofragment distributions and report two velocity components for each state. Regarding the faster components, both velocity and angular distributions are characterized by our results, while the slower components were not observed as such in our experiment, but slow to arise to the overlapped signals in the time domain, originated by the two isotopes of bromine atom, 79 Br and 81 Br, occurring in nature with approximately equal abundance; in the present experiment the two signals are almost isolated on sliced images by using the weak ion extraction field.…”
Section: Introductionmentioning
confidence: 99%
“…Both photofragments can be observed separately by resonance-enhanced multiphoton ionization (REMPI). Recent studies with nonoriented molecules have reported 38,39 that these two states show independent photofragment distributions and report two velocity components for each state. Regarding the faster components, both velocity and angular distributions are characterized by our results, while the slower components were not observed as such in our experiment, but slow to arise to the overlapped signals in the time domain, originated by the two isotopes of bromine atom, 79 Br and 81 Br, occurring in nature with approximately equal abundance; in the present experiment the two signals are almost isolated on sliced images by using the weak ion extraction field.…”
Section: Introductionmentioning
confidence: 99%